IDENTIFIKASI TINGKAT KERENTANAN ANCAMAN BENCANA LETUSAN GUNUNG MERAPI DI KOTA YOGYAKARTA - Sudirman, Sudirman Sudirman; Rizkianto, Tito Sigit; Rohmana, Rohmana; Muzani, Muzani (Jurnal Geografi, 2025)
This study aims to identify the level of vulnerability of Yogyakarta City to the eruption of Mount Merapi by looking at four main factors: social, economic, physical, and environmental. The method used is secondary data analysis obtained from literature review and previous research, as well as the calculation of the vulnerability index based on BNPB Regulation No. 2 of 2012. The results of the study show that almost all sub-districts in Yogyakarta have high social vulnerability, influenced by low levels of education, limited access to information, and a high number of vulnerable groups such as children, the elderly, and low-income communities. Physical vulnerability is also quite high due to inadequate infrastructure and lack of evacuation routes. In terms of economy, most sub-districts show low to moderate vulnerability, although some areas are still dependent on certain sectors. Environmental aspects show low vulnerability, but long-term threats such as ecosystem damage due to volcanic ash still need to be considered. This study recommends mitigation measures in the form of strengthening social capacity, improving infrastructure, and diversifying the economy.